2022
DOI: 10.1177/15589447211073977
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Trends at Hand Surgery Fellowships

Abstract: Background: Fellowship directors (FDs) influence the future of trainees in the field of hand surgery. Currently, there are no studies that analyze the demographic background, institutional training, and academic experience of hand surgery FDs. This study aims to serve as a framework to understand the landscape of current leadership positions in hand surgery education and to identify opportunities to improve FD diversity. Methods: The American Society for Surgery of the Hand Fellowship Directory was reviewed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Election of leaders with diverse training backgrounds, abilities, and accomplishments may help promote the vitality of hand surgery as a discipline. 9,17,18 Results from our study demonstrated that hand surgery presidents possess diverse training experiences and high levels of scholarly impact as measured by the h-index, which exceeded that of professors in hand surgery fellowship programs. 12 We confirmed our hypothesis as more plastic surgery presidents served in the AAHS than ASSH.…”
Section: Discussionmentioning
confidence: 74%
“…Election of leaders with diverse training backgrounds, abilities, and accomplishments may help promote the vitality of hand surgery as a discipline. 9,17,18 Results from our study demonstrated that hand surgery presidents possess diverse training experiences and high levels of scholarly impact as measured by the h-index, which exceeded that of professors in hand surgery fellowship programs. 12 We confirmed our hypothesis as more plastic surgery presidents served in the AAHS than ASSH.…”
Section: Discussionmentioning
confidence: 74%
“…This trend has been seen in other surgical specialties where women are taking on residency and fellowship directorships with fewer years in practice. 12,15 Increasing female representation among FDs was correlated with increasing female representation among fellows. This trend accords with studies across specialties that demonstrate how leadership equality may drive progress on other fronts.…”
Section: Discussionmentioning
confidence: 96%
“…This pattern may influence applicants with leadership ambitions to gravitate toward certain programs. 15 Further research is needed to understand why MMS FDs are more likely to have graduated from certain programs, ranging from the programs' training curricula, professional networks, and institution reputation to their likelihood of accepting applicants with inclinations for leadership. 14,16,25 A substantial number of FDs were appointed at the institutions where they completed their own fellowships, suggesting that MMS FDs have a hiring advantage at their training institutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations